Revision of the New Guinean genus Zophiuma (Hemiptera, Lophopidae) - Soulier-Perkins, Adeline; Cesne, Maxime Le (Zootaxa, 2021)
The lophopid genus Zophiuma Fennah, 1955 is revised with two new species described, Z. gitauae sp. nov. and Z. torricelli sp. nov. and Z. doreyensis (Distant, 1906) is placed in synonymy with Z. pupillata (Stål, 1863). A key to the species for the genus, distribution map and the male genitalia illustrations are provided.